2000
DOI: 10.1090/s0894-0347-00-00357-x
|View full text |Cite
|
Sign up to set email alerts
|

Large character sums

Abstract: We make conjectures and give estimates for how large character sums can be as we vary over all characters mod q q , and as we vary over real, quadratic characters. In particular we show that the largest sums seem to depend on the value of the character at “smooth numbers”.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 13 publications
1
86
0
2
Order By: Relevance
“…Our proofs of Theorems 1 and 2 are by the method of moments. Unfortunately, Granville and Soundrarajan [2] have shown that the fourth moment of the full sum (1•1) does not converge as x → ∞, so that this method yields no information about the distribution of (1•1). Following our proofs of Theorems 1 and 2 we present the results of some Monte Carlo experiments concerning the whole sum (restricted to squarefree numbers), which seem to suggest that its limiting distribution is not Gaussian.…”
Section: Bob Houghmentioning
confidence: 99%
See 3 more Smart Citations
“…Our proofs of Theorems 1 and 2 are by the method of moments. Unfortunately, Granville and Soundrarajan [2] have shown that the fourth moment of the full sum (1•1) does not converge as x → ∞, so that this method yields no information about the distribution of (1•1). Following our proofs of Theorems 1 and 2 we present the results of some Monte Carlo experiments concerning the whole sum (restricted to squarefree numbers), which seem to suggest that its limiting distribution is not Gaussian.…”
Section: Bob Houghmentioning
confidence: 99%
“…Indeed, the inequality may be checked by interchanging the order of the iterated integrals. When t j is the innermost integral its range of integration is from 3/2 to some function of the other variables, and on such a range the integral against dπ(t j ) is majorized by the integral against the smooth measure dt j /log t j + αdt j /(log t j ) 2 . Switching measures one at a time we make a sequence of changes that always increases the result.…”
Section: Main Lemmamentioning
confidence: 99%
See 2 more Smart Citations
“…Dans , améliorant des estimations de , Hough établit une minoration de la quantité Δfalse(x,qfalse):=trueprefixmax0ptχχ0χ mod qSfalse(x,χfalse),lorsque q est un nombre premier. Notant x=qϑ, cette estimation est valide dans le domaine 4 log 2q log q log 3qϑ14 log 2q log q log 3q.…”
Section: Introduction Et éNoncé Des Résultatsunclassified